1988
DOI: 10.1212/wnl.38.3.476
|View full text |Cite
|
Sign up to set email alerts
|

Free cytoplasmic Ca ++ at rest and after cholinergic stimulus is increased in cultured muscle cells from Duchenne muscular dystrophy patients

Abstract: We used a fluorescent dye, quin 2, to measure intracellular free calcium ([Ca++]i) in cultured skeletal muscle cells and skin fibroblasts from five Duchenne muscular dystrophy (DMD) patients and from five controls. We observed an enhanced [Ca++]i level, at rest and after acetylcholine (ACh) stimulation, in DMD muscle cells, but we did not detect any difference between DMD and normal skin fibroblasts. The abnormally higher [Ca++]i transient induced by ACh suggests that it plays a critical role in muscle degener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(36 citation statements)
references
References 0 publications
3
32
0
1
Order By: Relevance
“…Recently another group has confirmed our findings of elevated [Ca21]i levels in mdx myotubes using fura-2 calibrated by saponin permeabilization in known extracellular calcium-EGTA/bis-(o-aminophenoxy)-N,N,N',N'-tetraacetic acid (BAPTA)-buffered solutions (Bakker et al, 1993). Other free calcium indicators like quin-2 (Mongini et al, 1988), indo-1 (Sarabia and Klip, 1989), and calcium-selective microelectrodes (Sanchez et al, 1988) showed significantly higher levels of [Ca2+]i in dystrophin-deficient muscle cells, although absolute levels can not be compared by these different methods. There are two other independent methods which indicate higher levels in mdx fibers and myotubes.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Recently another group has confirmed our findings of elevated [Ca21]i levels in mdx myotubes using fura-2 calibrated by saponin permeabilization in known extracellular calcium-EGTA/bis-(o-aminophenoxy)-N,N,N',N'-tetraacetic acid (BAPTA)-buffered solutions (Bakker et al, 1993). Other free calcium indicators like quin-2 (Mongini et al, 1988), indo-1 (Sarabia and Klip, 1989), and calcium-selective microelectrodes (Sanchez et al, 1988) showed significantly higher levels of [Ca2+]i in dystrophin-deficient muscle cells, although absolute levels can not be compared by these different methods. There are two other independent methods which indicate higher levels in mdx fibers and myotubes.…”
Section: Discussionsupporting
confidence: 65%
“…On the other hand, total calcium (Bertorini et al, 1982;Dunn and Radda, 1991) and intracellular free calcium ([Ca21]i) concentrations (Mongini et al, 1988;Sanchez et al, 1988;Turner et al, 1988;Bakker et al, 1993) were found to be significantly elevated in muscle tissues lacking dystrophin.…”
Section: Introductionmentioning
confidence: 99%
“…The intracellular free Ca 2+ concentration, [Ca 2+ ], is elevated in the muscular dystrophies and other muscle pathologies, and this elevated intracellular [Ca 2+ ] evidently stimulates calpain activity (Mongini et al 1988;Turner et al 1988Turner et al , 1991Hopf et al 1996). The structural changes observed in rapidly atrophying muscles (Cullen and Pluskal 1977;Cullen and Fulthorpe 1982) are mimicked closely by treatment of myofibrils from normal muscle with µ-calpain (Dayton et al 1981;Goll et al 1991Goll et al , 1992b or m-calpain (Dayton et al 1975(Dayton et al , 1976bGoll et al 1991Goll et al , 1992b.…”
Section: Role Of the Calpain System In Skeletal Muscle Growthmentioning
confidence: 99%
“…Due to its similarities to structural proteins such as spectrin it has been hypothesized that dystrophin plays a role in mechanically stabilizing the muscle membrane (Brown & Hoffman, 1988). Dystrophin-negative myotubes and adult muscle fibres have been shown to have an elevated resting cytosolic [Ca2+] (Mongini et al 1988; Turner, Westwood, Regen & Steinhardt, 1988;Fong, Turner, Denetclaw & Steinhardt, 1990). This elevated calcium concentration could arise either because the dystrophin-deficient membranes are more fragile allowing calcium entry (Menke & Jockusch 1991), or because of abnormal functioning of calcium ion channels in the sarcolemma.…”
Section: Introductionmentioning
confidence: 99%